Sedimentary characteristics and evolution of Domanik facies from the Devonian–Carboniferous regression in the southern Volga-Ural Basin. (September 2020) - Liang, Xinping; Jin, Zhijun; Philippov, Victor; Obryadchikov, Oleg; Zhong, Dakang; Liu, Quanyou; Uspensky, Boris; Morozov, Vladimir
Abstract: The Domanik facies are organic matter-rich siliceous–clay–carbonate sediments of Upper Devonian to Lower Carboniferous age in the Volga-Ural and Timan-Pechora petroleum provinces. Different studies have been inferred for these sediments across the Eastern European (Russian) Platform, such as sedimentary environments, tectonic and hydrogeological regimes, paleotemperature changes and so on. However, less attention are paid to the petroleum formation in this area, especially that the link between low amplitude uplift and petroleum concentrated into fractured zones in the center of the sags is not clear. In this study, we particularly explained this relationship from analyzing the sedimentary evolution of the Domanik facies in the southern Volga-Ural Basin (southeastern Russian Platform). The results show that the sediments in this area were formed during a period of regression in uncompensated sags and depressions from the Middle Frasnian Semiluksk Chron (Late Devonian) until the Early Tournaisian (Early Carboniferous). The Semiluksk Formation in this area is dominated by typical Domanik carbonate sediments, which are dark, siliceous, clayey and bituminous, with complex faunal assemblages. From the Upper Frasnian – Lower Tournaisian, carbonates are developed and become less abundant as the axial parts of the Kama–Kinel sags narrow. We propose that during the formation of the Domanik facies when the basin reached anomalous isostatic gravity, the reefs that grew widely on the slope subsided due to the differential compaction of the basin, at the same time the center of the basin underwent uplift. This process formed tectonic fractures and petroleum could migrate and concentrate in the low-amplitude intrabasinal uplifts. Therefore, these uplifts could be characterized by maximal basin thicknesses, sediments with high petroleum concentrations and abnormally high pressure, and thus could be reasonable zones for the exploration and development of low porosity and low permeability Domanik reservoirs. Highlights: The sedimentary features of Domanik facies from the Volga–Ural Basin on the Russian Platform is described. An evolutionary model of Upper Devonian–Lower Carboniferoussediments is established. Main factors controlling the accumulation of petroleum are proposed. Zones for future exploration and development of Domanik reservoirs are suggested.